The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12885-020-07109-4
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcome of anastomotic leakage in patients undergoing low anterior resection for rectal cancer

Abstract: Background: The influence of anastomotic leakage (AL) on local recurrence rates and survival in rectal cancer remains controversial. The aim of this study was to analyze the effect of asymptomatic anastomotic leakage (AAL) and symptomatic anastomotic leakage (SAL) on short-and long-term outcome after curative rectal cancer resection. Methods: All patients who underwent surgical resection of non-metastatic rectal cancer with curative intent from January 2005 to December 2017 were retrospectively analyzed. Short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 46 publications
0
11
1
1
Order By: Relevance
“…For rectal surgery, laparoscopic approach was the standard approach. For T4 tumors, open approach was preferred [31]. A medial-to-lateral approach was used.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…For rectal surgery, laparoscopic approach was the standard approach. For T4 tumors, open approach was preferred [31]. A medial-to-lateral approach was used.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…A medial-to-lateral approach was used. Specimens were retrieved from abdominal cavity via a small abdominal incision [31]. Mechanical colorectal or manual colo-anal anastomoses (side-to-end or end-to-end) were performed depending on tumor level.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…AL is one of the common postoperative complications of rectal cancer. It has been reported that AL increases the risk of systemic, peritoneal, and local recurrence of CRC [ 12 , 13 ], and the possible mechanism is that the inflammatory reaction results in an increase in proinflammatory and proangiogenic factors, which may stimulate the growth of residual tumor cells. In addition, inflammation caused by AL contributes to tumor escape immune surveillance by suppressing T cell [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…AL not only causes serious perioperative consequences, such as pelvic abscesses, peritonitis, septic shock, and even death, but is also the main risk factor of long-term complications, such as postoperative anastomotic stenosis and bowel dysfunction. 4 , 5 Although surgical techniques and technologies and perioperative care have greatly evolved over the last several decades, AL is still the main challenge, especially for elderly patients. Compared with open surgery, laparoscopic surgery can significantly reduce the incidence of AL; however, there is no difference in the AL incidence between the techniques.…”
Section: Introductionmentioning
confidence: 99%